Variant Forks - Motivations and Impediments - Businge, John; Zerouali, Ahmed; Decan, Alexandre; Mens, Tom; Demeyer, Serge; De Roover, Coen (IEEE, 2022)
Social coding platforms centred around git provide explicit facilities to share code between projects: forks, pull requests, cherry-picking to name but a few. Variant forks are an interesting phenomenon in that respect, as they permit for different projects to peacefully co-exist, yet explicitly acknowledge the common ancestry. Several researchers analysed forking practices on open source platforms and observed that variant forks get created frequently. However, little is known on the motivations for launching such a variant fork. Is it mainly technical (e.g., diverging features), governance (e.g., diverging interests), legal (e.g., diverging licences), or do other factors come into play? We report the results of an exploratory qualitative analysis on the motivations behind creating and maintaining variant forks. We surveyed 105 maintainers of different active open source variant projects hosted on GitHub. Our study extends previous findings, identifying a number of fine-grained common motivations for launching a variant fork and listing concrete impediments for maintaining the co-existing projects.
Keywords: Mainlines; Variants; GitHub; Software ecosystems; Maintenance; Variability